Pelatihan Peningkatan Literasi Komputer Bagi Siswa - Pin Panji Yapinus; Marvin Chandra Wijaya; Hendry Wong; Jimmy Agustian Loekito; Jonathan Chandra (STKIP Andi Matappa, 2022)
The aim of this training is to improve students' abilities in computer skills and knowledge. This training is divided into six meetings in order to deliver the material well. The method used in this training is a distance learning system. This training teaches skills and knowledge in the fields of hardware, software, typing training using a computer and writing correspondence using a computer. The results of the evaluation of each meeting showed that the absorption capacity of the training participants increased with each meeting. In the final evaluation for the training participants, the score for computer skills (typing and correspondence) was 81% and basic computer knowledge was 90%.